Potential Changes in the Suitable Distribution Areas of Fagus orientalis Lipsky in Kastamonu Due to Global Climate Change - Erturk, Nihat; Aricak, Burak; Yigit, Nurcan; Sevik, Hakan (Aves, 2024)
The present study aims to determine the current distribution areas of Fagus orientalis Lipsky and the changes in suitable distribution areas due to global climate change within the borders of Kastamonu Forest Regional Directorate of Forestry. In the present study, the current suitable distribution areas of Fagus orientalis and the suitable distribution areas in the years 2040, 2070, and 2100 according to socioeconomic pathway 126, socioeconomic pathway 370, and socioeconomic pathway 585 scenarios were determined. The study results indicate that the suitable distribution areas of Fagus orientalis populations in Kastamonu will change depending on the effects of climate change and that the change will be in the form of an increase in general.
Keywords: Beech; Fagus orientalis Lipsky; global climate change (GCC); SSP scenarios